Moving Millennials out of the too hard basket: Exploring the challenges of attracting Millennial tourists to rural destinations. (March 2021) - Lewis, Clifford; Nelson, Kim; Black, Rosemary
Abstract: This paper explores the challenges rural destination marketers encounter when targeting the Millennial segment, which is an increasingly critical cohort for the tourism industry, due to their high-income levels, mobility associated with early life stage, and longevity as a market segment. Underpinned by Generational Theory and guided by an interpretivist approach, thirteen tourism destination marketers in regional Australia were interviewed to gain insight into their experiences and perception of Millennial travellers. The data revealed two distinct sets of characteristics relating to the Millennial target market, and the destination's capabilities, which together contributed to the identification of five marketing challenges rural destination marketers face when attempting to attract Millennials visitors. This research draws focus to a gap between what rural destination marketers perceive Millennials want and what rural destination can offer, which, compounded by challenges communicating with the Millennial segment, results in Millennials being considered a challenging audience for regional tourism destinations to attract.